Pengaruh pembelajaran drill and practice terhadap kemampuan pemecahan masalah matematis siswa - Tussakynah, Wafiah; Sormin, Masdelima Azizah; Samosir, Benny Sofyan (Jurnal Pendidik Indonesia, 2024)
This study aims to analyze the impact of the Drill and Practice teaching method on students' mathematical problem-solving abilities in quadratic equations and functions in grade XI Perbankan and XI TKR at SMK Negeri 4 Padangsidimpuan. The results show that implementing the Drill and Practice method significantly improved students' mathematical problem-solving abilities. The average initial ability score (pretest) was 59, which was below the mastery level. After learning with the Drill and Practice method, the average score increased to 76, exceeding the mastery level, with an improvement of 17 points. Statistical tests revealed a significant influence of the Drill and Practice method on students' mathematical problem-solving abilities. The t-test calculation produced a tvalue of 26.09, which is greater than the ttable value of 1.70 (tvalue > ttable​). Thus, the hypothesis that the Drill and Practice method positively influences students' mathematical problem-solving abilities is accepted.